Miguel de Unamuno. Pomiędzy fikcją a rzeczywistością - Kłosińska-Nachin, Agnieszka (Wydawnictwo Naukowe UAM, 2007)
The article Miguel de Unamuno. Pomiędzy fikcją a rzeczywistością (Miguel de Unamuno. Between fiction and reality) is an author's metalepsy analysis, a phenomenon described by Gerard Cenette (Mśtalepse. De la figurę k la fiction, 2004), in three texts by Miguel de Unamuno: Vida de Don Quijote y Sancho (1905), Niebla (1914) and Cómo se hace una novela (1927). Author's metalepsy, defined as transgression of the limits of fiction by an author, existentional metalepsy (understood as a vision of the world based on doubt, concerning the status of reality) and reader's metalepsy (if he’s forced to transgression of the limits of fiction) are the inseparable parts of Unamuno's writing.
Miguel de Unamuno. Between fiction and reality